Fostering English Speaking Atmosphere for Non English Students Department through English Courses - Yayuk Prasetiya; Muhimatul Ifadah; Siti Aimah (Universitas Muhammadiyah Semarang, 2017)
This research discussed about the influence of picture & picture and three minutes review in English course to students‘ speaking competence for non English department student. By comparing two teaching strategies; theimplementation of picture and picture or three minutes review and conventional teaching method. This research used quantitative approach with experimental method. The population was thestudents of Rusunawa (students‘ dormitory) Unimus Semarang. The sample was the students of class C4 and A2 with the amount of 24 students in each class. The researcher took the sampling based on random sampling, with C4 as the experimental group and A2 as the control group. The research instruments used were the test and questionnaire. The result of the test was ???? ???????????????????????????????????? ???????????? greater than ???? ????????????????????, so the hypothesis was accepted. There was significant difference in students‘ speaking competence between class taught with picture and picture or three minutes review and conventional teaching method that is 8.75. However, it was found that non –English students has various obstruction to join the English Courses. Time availability becomes one of those, because those students come from several backgrounds of study, and the schedule of English courses cannot be managed firmly. The courses were done to make the students getting used to that are why the schedule is made flexible, depend on the students‘ feasibility in joining the course.However, through many activities in the dormitory through the course showed positive foster in learning English, even though those students have different challenges.